Los hongos de Colombia - IV. Bisporella Triseptata and its allies in Colombia Los hongos de Colombia - IV. Bisporella Triseptata and its allies in Colombia - Carpenter S. E.; Dumont K. P. (Caldasia)
During the combined mycological explorations of Colombia by the Instituto de Ciencias Naturales (Bogotá), Instituto Colombiano Agropecuario (Bogotá) and The New York Botanical Garden, many new and interesting fungi have been discovered. Among these, several collections of an apparently rare and poorly known species of Bisporella Sacc. were made, which are worthy of report. During the combined mycological explorations of Colombia by the Instituto de Ciencias Naturales (Bogotá), Instituto Colombiano Agropecuario (Bogotá) and The New York Botanical Garden, many new and interesting fungi have been discovered. Among these, several collections of an apparently rare and poorly known species of Bisporella Sacc. were made, which are worthy of report.